Predictors, Types of Internet Use, and the Psychological Well-Being of Older Adults: A Comprehensive Model. (14th March 2022) - Rosell, Javiera; Vergés, Alvaro; Miranda-Castillo, Claudia; Sepúlveda-Caro, Sofía; Gómez, Macarena
Abstract: Objectives: This study aims to evaluate a comprehensive model that includes predictors of use, types of Internet use, and psychological well-being outcomes in the older population. Methods: The total sample comprised 650 older Internet users. Structural equation modeling was used to estimate the effect of predictors (i.e., effort expectancy, performance expectancy, social influence, and ageism) on types of Internet use (i.e., information seeking, communication, instrumental use, and leisure) and the impact of the type of use on the psychological well-being of older adults (i.e., depressive and anxious symptomatology). In addition, the indirect effect of different types of Internet use was evaluated, that is, they were considered as mediator variables. Results: Effort expectancy, social influence, and ageism predicted different types of Internet use. The relationship between effort expectancy and anxious symptomatology had an indirect effect via information seeking, whereas the relationship between ageism and anxious symptomatology showed an indirect effect via leisure. Discussion: The findings support the importance of differentiating the types of Internet use to understand its impact on psychological well-being. Information seeking is associated with anxious symptomatology and is predicted by effort expectancy. On the contrary, leisure is crucial because of its relationship with anxious symptomatology, and less ageism can promote it. This information is useful for developing effective interventions that promote the well-being of older adults through the Internet, including strategies to cope with some online challenges that could lead to negative consequences, such as information overload.